Characterization of the sedimentary deposits of cÁssia and its relationship with the cÁssia fault zone, southwest of minas gerais - Sartori, José Eduardo [UNESP]; Arai, Mitsuru [UNESP]; Morales, Norberto [UNESP]; de QUADROS, Letícia Severina [UNESP] (UNESP - Universidade Estadual Paulista, 2019)
The sedimentary deposits of the Cássia region in southwestern Minas Gerais are known and intensely exploited as raw material for red ceramics since the 1930s. However, such geological materials have been poorly studied, generally succinctly in works still unpublished. In addition, the sedimentary cover is strongly controlled by the traces of the Cássia Fault Zone, an important preCambrian structure that cuts and deforms the crystalline basement of the region. In this context, the present work has the objective of describing and mapping the sedimentary deposits, investigating their relation with the fault zone. It was characterized a sedimentary package of predominantly pelitic composition, related to the registration of a paleolake with the episodic and localized entry of alluvial fans associated with the tectonic movement/reactivation of the traces of the Cássia Fault Zone during the Quaternary.
Caracterização dos depósitos sedimentares de cássia e sua relação com a zona de falha de cássia, sudoeste de minas gerais
Keywords: Fault Reactivation; Neotectonics; Palinology; Quaternary